Developing a Pedagogical Content Knowledge (PCK) Assessment for Pre-Service Arabic Language Teachers - Maziyah, Laily; Faizin, Nur; Alfan, Muhammad (Jurnal Kiprah Pendidikan, 2025)
This study aims to develop an PCK assessment for pre-service Arabic language teachers. The analysis focused on the quality of the Indonesian-language try-out items, considering parameters such as difficulty level, discrimination power, validity, distractor effectiveness, and instrument reliability. Data were collected from the responses of 291 try-out participants to 35 multiple-choice items. The analysis involved calculating difficulty indices, discrimination indices, item-total correlations, evaluating distractor effectiveness, and testing reliability using Cronbach’s Alpha. The findings revealed that most items fell into the moderate difficulty category, while the instrument demonstrated a fairly good level of reliability. Nonetheless, several items were identified as requiring revision to enhance the overall quality of the evaluation instrument.